Long run forecasts of Australia's terms of trade - Jared Bullen; Michael Kouparitsas; Michal Krolikowski (The Australian Government, The Treasury, 2014)
Australia's terms of trade rose significantly over the eight years to 2011 12 following a period of relative constancy over the preceding 40 years. Australian Government fiscal projections from the 2010 11 Budget to the 2013 14 Budget, assumed that beyond the near term forecast period the terms of trade would fall by 20 per cent over the subsequent 15 years. This approach was silent on when the expected decline would end and the level at which the terms of trade would eventually settle. This paper details the projection methodology underlying the terms of trade projection assumption in the 2013 14 MYEFO. In contrast to the earlier approach it provides guidance on the timing of the end of the current expected decline and the associated long run level of the terms of trade. The centrepiece of the new approach is detailed price and volume forecasting modules for Australia's major export categories, including global demand and supply models for the three major bulk commodities (iron ore, metallurgical coal and thermal coal). Based on this methodology, Australia's terms of trade are expected to fall at a more rapid rate than previously predicted in the 2013 14 Budget from 2012 13 to 2017 18 and remain reasonably constant thereafter at a level roughly equal to that recorded in 2006 07. As noted in the 2013 14 MYEFO, there are a number of downside risks to this outlook including uncertainty around the global economy, the nominal exchange rate and non-bulk commodity price forecasts. Applying prudent judgement to the model's outcome results in a long-run terms of trade that settles at the level observed in 2005 06 by 2019 20.
Keywords: Q00; F17; E37; 330; Confidence commodity prices; production cost; mining boom